Pengaruh pH larutan elektrolit terhadap kuat lekat dan ketebalan hasil elektroplating bahan baja karbon rendah - Asroni, Asroni; Handono, Sulis Dri; Wahyudi, Tri Cahyo; Saputra, Yogi (Universitas Muhammadiyah Metro, 2021)
Electroplating is a process of coating a solid material with a metal layer using an electric current through an electrolyte solution. The purpose of this study was to obtain the best solution pH for the thickness and adhesive strength results of electroplating, as well as the method used in various electrolyte solutions, namely pH 1.7, pH 3, pH 5, pH 7 and pH 9. The anode was used Nickel while the cathode uses ST41 Steel with dimensions of 70 mm x 50 mm x 10 mm. The distance between the anode and cathode is 10 cm and a DC current voltage of 5.5 volts with an immersion time of 20 minutes. The best coating were obtained at a variation of pH 1.7 with a result of 0.0322 mm and adhesive strength at a variation of pH 5 with a result of 26.53 MPa and pH 7 of 24.25 MPa.Keywords: Electroplating, pH variation, adhesion strength, thickness, Steel ST41, Nickel.